Pemantauan Detak Jantung Berbasis Sensor MAX30102 - Alkhoir, Qonita; Alfarizy, Firnas; Dwinugroho, Fahrul Ridho; Taryudi; Sari, Churnia (LPPM Universitas Negeri Jakarta, 2026)
Heart rate monitoring is an important effort in maintaining cardiovascular health, considering that heart rhythm disorders such as bradycardia and tachycardia can pose serious health risks if not detected early. This study designs and implements a heart rate monitoring system based on the photoplethysmography (PPG) method using an optical sensor capable of measuring heart rate in real time, displaying values in beats per minute (BPM), and classifying heart rate conditions into bradycardia, normal, and tachycardia categories. The test results show that the system produces stable heart rate readings with an average error of 3.86%, resulting in a measurement accuracy of 96.14% under resting conditions. The developed system is simple, portable, and low-cost, making it a potential solution for independent health monitoring and early detection of heart rhythm disorders. Keywords: Heart rate, photoplethysmography, monitoring system, cardiovascular health